Fatores de adoção de sistemas agroflorestais por agricultores familiares do município de Medicilândia, Pará - CALVI, Miquéias Freitas (Universidade Federal do Pará, 2021)
Agroforestry Systems (SAFs) is an alternative to the conventional agricultural practices and use of the soil still little employed by family farmers, however, with great economical and environmental importance. To motivate implantations of these alternative systems is relevant due the concerns with the biodiversity conservation and global climatic changes. The cocoa tree is an appropriate crop to be established in SAFs systems due the need of shadow of this crop, being the municipality of Medicilândia, West of the State of Pará, Brazil, one of the main poles of cocoa production from Brazil. Aiming to understand which factors contribute and/or limit the use of SAFs as productive activity in the municipality of Medicilândia, in our study we applied questionnaires with objective and subjective questions to 73 farming families, approaching the specificities of all these families, their farms, access to the public politics, and commercialization of products from agriculture and SAFs. In this study were identified 164 arrangements of these Agroforestry systems, with their ages varying between 4 and 38 years. The main factors that support the adoption of SAFs by farmers from Medicilândia, PA, are related to the economical and productive aspects, being the market existence and increase of income by farmers factors that highlight this adoption. In contrast, the main limitation refers to the inadequacy and low quality of the services offered by public technical support, which affects directly the production of these systems once the administration of SAFs without technical support can reduce, considerably, the productivity of the crops.